The mineral clouds on HD 209458b and HD 189733b. Issue 1 (20th April 2016) - Helling, Ch.; Lee, E.; Dobbs-Dixon, I.; Mayne, N.; Amundsen, D. S.; Khaimova, J.; Unger, A. A.; Manners, J.; Acreman, D.; Smith, C.
Abstract: 3D atmosphere model results are used to comparatively study the kinetic, non-equilibrium cloud formation in the atmospheres of two example planets guided by the giant gas planets HD 209458b and HD 189733b. Rather independently of hydrodynamic model differences, our cloud modelling suggest that both planets are covered in mineral clouds throughout the entire modelling domain. Both planets harbour chemically complex clouds that are made of mineral particles that have a height-dependent material composition and size. The remaining gas-phase element abundances strongly affect the molecular abundances of the atmosphere in the cloud-forming regions. Hydrocarbon and cyanopolyyne molecules can be rather abundant in the inner, dense part of the atmospheres of HD 189733b and HD 209458b. No one value for metallicity and the C/O ratio can be used to describe an extrasolar planet. Our results concerning the presence and location of water in relation to the clouds explain some of the observed difference between the two planets. In HD 189733b, strong water features have been reported while such features appear less strong for HD 209458b. By considering the location of the clouds in the two atmospheres, we see that obscuring clouds exist high in the atmosphere of HD 209458b, but much deeper in HD 189733b. We further conclude that the (self-imposed) degeneracy of cloud parameters in retrieval methods can only be lifted if the cloud formation processes are accurately modelled in contrast to prescribing them by independent parameters.